Istihsan Dalam Madhhab Shafi'i: Tinjauan Atas Kasus Mustathnayat Madhhab Shafi'i dalam Perspektif Istihsan Madhhab Hanafi - Abdul Mun'im Saleh (Justicia Islamica, 2019)
Istihsan is a dalil (source and method) of Islamic law validated by the Hanafi school. Al-Shafi’i strongly rejected istihsann (juristic preference) and considered those who practice it as trying to compete with God as the Ultimate Authority and taking a careless decision. However, the istihsan way of thinking in the Shafi’i school is not uncommon but is considered valid. In the discipline of al-qawa’id al-fiqhiyah (Islamic legal maxims), the existence of mustathnayat (exceptions) cases with istithna’ (exception) method is showing istihsan method. This research compares mustathnayat/exception cases in qawa’d al-fiqhiyyah in Shafi’i madhhab and istihsan in Hanafi madhhab. The origin of the legal decision of exception in mustahnayat is judged from istihsan’s point of view. This research accepts that mustathnayat cases in Shafi’i madhhab result from thinking methods like istihsan in Hanafi madhhab in all aspects (its reality, method, and purpose).